2021
DOI: 10.1016/j.injury.2021.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic fractures of hip and knee–A morbidity and mortality analysis

Abstract: Background: Periprosthetic fractures (PPF) following total knee (TKA) and hip arthroplasty (THA) have become more common over the years. The aim of the present study was to assess morbidity and mortality following surgery for PPF of hip and knee.Patients and methods: Altogether, 124 patients (mean age: 77 years; 77.4% female) with PPF of the hip ( n = 97) and knee ( n = 27), treated between 2005 and 2017 at a level-1 trauma centre, were retrospectively included. In order to assess risk factors for postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“… 20 Another retrospective study of 124 patients with PPF of the hip and knee found that sex, type of fixation, surgical delay, BMI, and age at surgery were not associated with increased mortality. 21 Few studies have analyzed mortality according to patient characteristics in patients with Vancouver type B fractures.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Another retrospective study of 124 patients with PPF of the hip and knee found that sex, type of fixation, surgical delay, BMI, and age at surgery were not associated with increased mortality. 21 Few studies have analyzed mortality according to patient characteristics in patients with Vancouver type B fractures.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies have provided mixed results regarding the association between the timing of surgery and postoperative mortality in elderly patients with distal femur fracture. Several observational studies found that early surgery was associated with reduced mortality [7][8][9], while other studies showed no such association [10][11][12][13]. One of the reasons for these conflicting results may be small patient numbers used in previous studies (n = 88 to 392) [2,3,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple surgical treatment techniques have been described for the treatment of periprosthetic femur fractures in the context of a total knee replacement. Supracondylar periprosthetic distal femur fractures associated with stable implants can be treated with open reduction internal fixation with uniplanar fixation using a fixed-angle device such as a lateral locking plate or angled blade plate [10][11][12][13]. Multiplanar fixation can also be used through a retrograde intramedullary nail, dualplating, or combinations of intra-and extramedullary fixation nails, plates, or allograft bone [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%